CICLO DE ESTUDOS EM EDUCAÇÃO FÍSICA - Carlan, Paulo; Schwengber, Maria S. V.; González, Fernando; Fensterseifer, Paulo E.; Silva, Sidnei P. d.; Burckardt, Eduarda V. (Salão do Conhecimento, 2013)
Resumo